Credit Risk Analysis of Ryanair - Oo, Moe Pwint; Ali, Tanweer; Rosecká, Nikola; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor thesis analyses the credit risk of Ryanair. The aim is to encompass wider macroeconomic, industry-specific and company-specific risks that impact credit risk of airlines. The study uses traditional, textbook methods rarely applied in the sea of highly quantitative credit risk assessments, such as 5Cs framework and credit scorecard. The analysis 5Cs (Character, Conditions, Capacity, Capital, Collateral and Covenants – the latter two grouped as one C) shows that Ryanair has low levels of debt, low willingness to take on debts unless necessary, and relies on their cash flows for expansion. The individual Cs are scored between 0-10 on a weighted credit scorecard. The final score is 7.58, indicating that Ryanair has low credit risk for the next fiscal year. Their overreliance on scandalous aircraft supplier Boeing is the main reason the score is closer to the lower bound of the low risk range (7-10). Top management is advised to include triggered contractual clauses of compensation for serious situations to help the airline with grave, financial consequences
Vedoucí práce: Tanweer Ali
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses